2011
DOI: 10.1007/s00402-011-1321-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of gentamicin-coated nails in the tibia: preliminary results of a prospective study

Abstract: BackgroundThe use of antibiotic-coated implants may reduce the rate of infection and facilitate fracture healing after surgical treatment of tibial shaft fractures. A new biodegradable gentamicin-loaded coating of an implant (UTN PROtect®) was CE-certified in August 2005. In this prospective, non-randomized case series, we investigated the clinical, laboratory and radiological outcomes of 21 patients who underwent surgical treatment in closed or open tibial fractures, as well as revisions with the UTN PROtect®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0
7

Year Published

2015
2015
2107
2107

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 22 publications
(45 reference statements)
3
130
0
7
Order By: Relevance
“…In a rabbit model, Alt et al [16] found that the gentamicin-HA composite provided a statistically significant reduction in infection rate when compared to uncoated total joint replacements. In patient trials, gentamicin-coated implants have displayed promising preliminary results ( Figure 1) [17][18][19][20] . Limitations of antibiotic coatings include the use of fixed, predetermined antibiotics; limited duration of drug elution; and the risk of developing drug resistance [21] .…”
Section: Antibiotic-based Coatingsmentioning
confidence: 99%
“…In a rabbit model, Alt et al [16] found that the gentamicin-HA composite provided a statistically significant reduction in infection rate when compared to uncoated total joint replacements. In patient trials, gentamicin-coated implants have displayed promising preliminary results ( Figure 1) [17][18][19][20] . Limitations of antibiotic coatings include the use of fixed, predetermined antibiotics; limited duration of drug elution; and the risk of developing drug resistance [21] .…”
Section: Antibiotic-based Coatingsmentioning
confidence: 99%
“…Metal-based drug eluting systems have received little attention in the literature in comparison to polymer-based systems. So far, only intramedullary nails with a PDLLA coating containing gentamicin were placed on the market [14]. For example, metal implants such as plates and wires have been coated with a polymer matrix layer loaded with a microbial antibiotic, while others have studied different therapeutic agents including triclosan and chlorhexidine (CHX) [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include passive and active antimicrobial coatings [4,9,19], surface modifications [10], and bioabsorbable sleeves that contain antimicrobials [16]. Data suggest that implant materials alone, such as black silicon and silicon nitride, may have the ability to prevent bacterial attachment or eradicate bacteria that come in contact with the material [7,10].…”
Section: Introductionmentioning
confidence: 99%